Robust circuit parameters design for the CLLC-type DC transformer in the hybrid AC-DC microgrid - Huang, Jingjing (2020)
CLLC-type dc transformer (CLLC-DCT) is very popular in the hybrid ac-dc microgrid thanks to its high-power density advantage and good bidirectional power transfer capacity. In the hybrid ac/dc microgrid, the open-loop control is always utilized by the CLLC-DCT to cooperate with the bidirectional interlinking converter to realize the power and voltage conversion between the ac and dc bus. This paper first studies the circuit parameters design of the open-loop controlled CLLC-DCT with consideration of such a realistic problem: The real inductors/capacitors values are actually different with their theoretically designed values due to the operation power and temperature variation. To solve this problem, a robust circuit parameters design scheme is proposed for the CLLC-DCT in this paper. With the proposed scheme, the designed CLLC-DCT exhibits good power transmission and voltage regulation ability in the hybrid ac/dc microgrid even when its actual inductors/capacitors values vary with the practical power and temperature. The robust design method is experimentally verified in a hybrid ac/dc microgrid prototype.